2005
DOI: 10.1081/pte-200062170
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urea on the Physico-Mechanical and Degradable Properties of Mercerized and Acid Hydrolyzed Coir (Cocos nucifera) Fibers Photocured with 1,6-Hexanediol Diacylate

Abstract: Coir fibers were modified with 1,6-hexanediol diacrylate (HDDA) by using ultraviolet (UV) radiation. Concentration of HDDA, soaking time, and radiation dose were optimized and found to be 30% HDDA in methanol along with photoinitiator Irgacure-500 (2%) and 120 min of soaking time the better performance registered as the optimum conditions, where polymer loading (PL) was 17% and tensile strength (TS) was 50%. Urea of different concentrations (0.5-2%) was incorporated with 30% HDDA to monitor its effect on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This means TS and TM increase with the decrease of monomer concentration and the increase of the content of solvent in the formulations. This could be regarded as a fact that in dilute formulations, the solvent can easily penetrate into the core of fibers, as a result, monomers can easily find out the sites on fiber for cross-linking or grafting, which consequently enhances the strength of composites [15]. Considering the formulations between F4 and F5, it was reported that the F5 treated jute fabrics showed higher mechanical properties because of the reduction of oligomer from 5 to 2.5%.…”
Section: Optimization Of Formulation and Radiation Dosementioning
confidence: 99%
See 1 more Smart Citation
“…This means TS and TM increase with the decrease of monomer concentration and the increase of the content of solvent in the formulations. This could be regarded as a fact that in dilute formulations, the solvent can easily penetrate into the core of fibers, as a result, monomers can easily find out the sites on fiber for cross-linking or grafting, which consequently enhances the strength of composites [15]. Considering the formulations between F4 and F5, it was reported that the F5 treated jute fabrics showed higher mechanical properties because of the reduction of oligomer from 5 to 2.5%.…”
Section: Optimization Of Formulation and Radiation Dosementioning
confidence: 99%
“…When the monomer concentration is increased, the amount of residual concentration is also increased and causes the faster rate of formation of threedimensional network structures causing restricted mobility. At higher monomer concentration, radical-radical recombination process may be dominating and the formation of homo-polymer rather than monomer-cellulose reaction may be prominent [15] resulting in the decrease in mechanical strength as compared to that at low monomer concentration. Both the TS and TM increase up to a certain value with the increase of radiation dose and then decrease.…”
Section: Optimization Of Formulation and Radiation Dosementioning
confidence: 99%
“…9,10 It was reported in the previous study that treatment of natural fibers with various monomers of different functionalities under UV irradiation improves their physical properties. [11][12][13][14][15] Ethylene glycol dimethacrylate (EGDMA) is one of the difunctional monomers that could be cured under UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…So, TS and TM of the composites increase with the increase of monomer concentration in the formulation solution with simultaneous decrease of solvent. In dilute formulations, solvent can easily penetrate into the core of fibers, as a result, monomers can easily penetrate in the fiber bundles thus enhancing cross-linking or grafting the monomer with jute during UV curing, which attributed higher mechanical properties of the composites [41]. Formulation F3 showed the higher mechanical properties.…”
Section: Optimization Of Formulation and Radiation Dosementioning
confidence: 99%